Theoretical and practical studies of the deformation properties of the ground - Burland, John Boscawen (My University, 1982)
This thesis consi~ts of sixteen papers - all of them concerned with the deformation properties of the ground. Much of the soil m~chanics literature is concerned with the strength of soils and ultimate conditions. This is understandable since the engineer's prime concern in design is to avoid collapse. However, the engineer is also much concerned with the behaviour of the ground under working conditions - usually well removed from failure. This requires knowledge of the deformation properties of the ground. Much of my research work has been devoted to this topic and it is natural that it should form the subject of the thesis. The papers fall into four broad categories: the behaviour of soft clays; the foundation properties of chalk; soil/structure interaction; movements around deep excavations in stiff clays. In addition, the first paper in the collection is concerned with the behaviour of bored piles in stiff clays. This was one of the first problems I was faced with as a practising engineer and the field that it opened up to me led me to go to Cambridge where I studied the latest theoretical work on the stress-strain behaviour of soft clays. After obtaining my PhD degree from Cambridge University I joined the Building Research Station. Much of my work there was concerned with field studies of the deformation of the ground in relation to a variety of civil engineering projects. It is perhaps worth emphasising tha~uch investigations are usually carried out in cooperation with consulting engineers and contractors and also involve large teams of researchers. I have always insisted that the contribution of collaborators should be recognised in the authorship of papers and it will be noted that most of my papers have co-authors. I have indicated in the thesis that co-authors have contributed to the preparation of a paper. The papers are grouped into five categories and I have prepared a short introduction to each grouping describing the development of the subject and highlighting the more important features. Appendix 1 gives a list of the papers contained in the thesis and in Appendix 2 I have listed my most important publications
A thesis submitted for the degree of Doctor of Science in Engineering.
Keywords: Deformation properties of the ground